Safety and impact of the Mediterranean diet in patients with chronic kidney disease: a pilot randomized crossover trial - Kwon, Yu-Jin; Joo, Young Su; Yun, Hae-Ryong; Lim, Li Rang; Yang, Juyeon; Lee, Hye Sun; Kim, Hyung-Mi; Lee, Hyangkyu; Lee, Jung Eun; Lee, Ji-Won (Frontiers in Nutrition, 2024)
Introduction Emerging evidence highlights the potential advantages of the Mediterranean diet (MD) in preserving kidney function and slowing chronic kidney disease (CKD) progression. However, interventional studies on the MD are scarce in East Asian populations. Methods This randomized crossover trial aimed to assess the safety and short-term impact of the Mediterranean Proper Optimal Balance (MEDi-POB) diet in Korean patients with stage 3–4 CKD. Kidney function was assessed using the estimated glomerular filtration rate, which was calculated using the CKD Epidemiology Collaboration equation. Fifty patients with CKD were randomly assigned to two groups, each starting with a different 4-week intervention, followed by a 4-week washout period, followed by a switch to the other 4-week intervention. During the MEDi-POB intervention, patients received home delivery of meals twice daily, 5 days a week, while the control intervention comprised a conventional diet. Forty-six patients successfully completed the entire 12-week trial. Paired t-tests were conducted to assess mean differences between the two groups. A linear mixed model was used to adjust for sequence and period. Results Dietary fat, fiber, and niacin intake were significantly higher following the MEDi-POB diet than following the control diet (p = 0.001 for fat, p < 0.001 for fiber, and p = 0.007 for niacin). The MEDi-POB diet also yielded slightly increased total CO2 levels (p = 0.043), indicating effective management of metabolic acidosis. Conversely, sodium and copper intake were significantly lower with the MEDi-POB diet (p = 0.032 and p = 0.037, respectively). Caloric intake increased, but body mass index slightly decreased from baseline after consuming the MEDi-POB diet. Dietary potassium intake exhibited a non-significant increase (p = 0.053), and no significant changes in serum (p = 0.883) and urine potassium levels (p = 0.087) occurred. Kidney function remained well-preserved following the MEDi-POB diet. Conclusion These results indicate that the MEDi-POB diet is safe even in patients with advanced CKD, as it does not adversely affect serum and urine potassium levels and helps maintain kidney function.